The food allergy war - Horizon (Television program) (London : BBC Enterprises, 1985)
Tells how recent British studies have confirmed that many food such as milk, eggs, corn, and wheat are responsible for many food allergies. Relates how the concept of food allergy has developed from the 1950s to the present and discusses a controversial cure for allergies, neutralization therapy
Keywords: Food allergy